Prevalence of head injury and associated factors among trauma patients visiting surgical emergency department of Gondar University Referral Hospital, Northwest Ethiopia 2016. Across-sectional study - Tarkie Abebe Walle; Bewket Tadesse Tiruneh; Debrework Tesgera Bashah (Elsevier, 2018)
Background: Traumatic head injury is a common and leading cause of presentations to emergency departments. The burden is prominent in low and middle income countries and the major cause of death and disability. Objective: To assess the prevalence of head injury and associated factors among trauma patients visiting surgical emergency department of Gondar University Referral hospital, Northwest Ethiopia, 2016. Methods: An institution-based cross-sectional study was employed with a total sample size of 260 participants from March to April 2016. The study was conducted at Gondar University Referral Hospital, Surgical Emergency Department. A systematic random sampling technique was employed. And the data checked for completeness, consistency and accuracy, entered to EPI info version 3.5.1 and imported to SPSS version 20 for analysis. Bivariate and multivariate logistic regressions were performed to identify factors associated with head injury. P < 0.05, and Odds ratio with 95% confidence interval were computed to determine the level of significance. Results: Out of 260 trauma cases, 105 (40.5%) were found to be head injuries. Being a male (AOR = 5.33; 95% CI, 2.095-13.57), being a daily labourer (AOR = 2.873; 95% CI, 1.56-22.090), being unintentional injury (AOR = 3.360; 95% CI, 1.08-10.46), being illiterate (AOR = 2.7; 95% CI, 1.007-7.47), and were statically significant. Conclusion: The prevalence of head injury was high and being male, being illiterate, a daily labourer and an unintentional injury were determinants. The appropriate prevention measure is the need to decrease the magnitude of head injuries. Keywords: Emergency department, Head injury, Trauma